Factors influencing ovulation and the risk of ovarian cancer in BRCA1 and BRCA2 mutation carriers. Issue 5 (18th December 2014) - Kotsopoulos, Joanne; Lubinski, Jan; Gronwald, Jacek; Cybulski, Cezary; Demsky, Rochelle; Neuhausen, Susan L.; Kim‐Sing, Charmaine; Tung, Nadine; Friedman, Susan; Senter, Leigha; Weitzel, Jeffrey; Karlan, Beth; et al.
<x xml:space="preserve">Abstract</x> The role of the lifetime number of ovulatory cycles has not been evaluated in the context of BRCA‐associated ovarian cancer. Thus, we conducted a matched case–control study to evaluate the relationship between the cumulative number of ovulatory cycles (and contributing components) and risk of developing ovarian cancer in BRCA mutation carriers (1, 329 cases and 5, 267 controls). Information regarding reproductive and hormonal factors was collected from a routinely administered questionnaire. Conditional logistic regression was used to evaluate all associations. We observed a 45% reduction in the risk of developing ovarian cancer among women in the lowest vs. highest quartile of ovulatory cycles (OR = 0.55; 95% CI 0.41–0.75, p = 0.0001). Breastfeeding for more than 12 months was associated with a 38% (95% CI 0.48–0.79) and 50% (95% CI 0.29–0.84) reduction in risk among BRCA1 and BRCA2 mutation carriers, respectively. For oral contraceptive use, maximum benefit was seen with five or more years of use among BRCA1 mutation carriers (OR = 0.50; 95% CI 0.40–0.63) and three or more years for BRCA2 mutation carriers (OR = 0.42; 95% CI 0.22–0.83). Increasing parity was associated with a significant inverse trend among BRCA1 (OR = 0.87; 95% CI 0.79–0.96; p‐trend = 0.005) but not BRCA2 mutation carriers (OR 0.98; 95% CI 0.81–1.19; p‐trend = 0.85). A later age at menopause was associated with an increased risk in women with a BRCA1 mutation (OR trend = 1.18; 95% CI 1.03–1.35; p = 0.02). These findings support an important role of breastfeeding and oral contraceptive use for the primary prevention of ovarian cancer among women carrying BRCA mutations.